A 2D Nearest-Neighbor Quantum Architecture for Factoring - Pham, Paul; Svore, Krysta M.; Svore, Krysta M. (Quantum Information and Computation, 2013)
We present a 2D nearest-neighbor quantum architecture for Shor's factoring algorithm in polylogarithmic depth. Our implementation uses parallel phase estimation, constant-depth fanout and teleportation, and constant-depth carry-save modular addition. We derive asymptotic bounds on the circuit depth and width of our architecture and provide a comparison to all previous nearest-neighbor factoring implementations.
Also available at http://arxiv.org/abs/1207.6655; also presented at Reversible Computing 2012